Umar Ibn-Khaththab pelaksanaan hukum Islam - Mohd Said Ishakl (Penerbit Universiti Teknologi Malaysia, 2000)
On Islamic law during the Umar Ibn al-Khaththab Caliph with reference to socio-political conditions in Malaysia.